Tri-Lineage Differentiation Potential of Stem Cells from Human Exfoliated Deciduous Teeth - An In-vitro Study - Ratna Yumkham; C Nagarathna; B. S. Shakuntala; Rajkumari Sarada; Gargi Yumnam; Bandana Waikhom (Journal of Pharmacy and Bioallied Sciences)
Background: The use of SHED might bring advantages for tissue engineering over the use of stem cells from adult human teeth as SHEDs were reported to have higher proliferation rate and increase cell population doublings as compared with stem cells from permanent teeth. Objective: The study’s objective was to assess the growth kinetics and tri-lineage differentiation capacity of stem cells derived from human exfoliated deciduous teeth. Material and Method: After being propagated through multiple sequential subcultures, adherent fibroblastic cells in the pulp tissue culture from human exfoliation teeth were evaluated to assess their tripotent differentiation potential into bone, cartilage, and adipose cell lineages. Result: The stem cells derived from dental pulp had a comparatively high ability for proliferation and successfully differentiated into chondrocytes and osteocytes while less significant for adipocytes. Conclusion: Stem cells from Human Exfoliated Deciduous teeth are mesenchymal stem cells which are multipotent and can serve as a promising incentive for therapeutic and future research purposes.